Inovasi Produk dan Kreativitas dalam Pengembangan UMKM Kesenian Batik Manggur di Triwung Kidul - Uhriyah, Sulfi; Agustin, Sylvia; Arifin, Mohammad (Al-DYAS, 2024)
Product Innovation and Creativity in developing Manggur batik art MSMEs in Triwung Kidul sub-district is an effort carried out by the owner of Manggur Batik MSMEs, namely Mrs. Malikha. The formulation of the research problem is how innovation and creativity of Maggur Batik products can develop batik art in Micro, Small and Medium Enterprises (MSMEs), namely by combining the results of local products and modern products so that this makes consumers interested in the products produced. by batik manggur and prioritizes product quality in terms of the raw materials used in the production process. This research aims to determine product innovation and creativity in developing arts MSMEs in Batik Manggur in Triwung Kidul sub-district. In this research, researchers hope that there will be many practical and theoretical benefits that will help in implementing new innovations and creativity in batik arts MSMEs. This research uses qualitative descriptive research with a purposive area approach as a technique for determining the location. in this case the research uses purposive sampling in batik product innovation and creativity. Purposive sampling was used in this research to determine the innovation and creativity of batik products. This kind of descriptive qualitative research uses a purposive area method for determining location.